Policy capacity matters for capacity development: comparing teacher in-service training and career advancement in basic education systems of India and China. (June 2021) - Yan, Yifei; Saguin, Kidjie
Capacity development is central to the study and practice of public policy and administration, but ensuring its effectiveness requires a substantial amount of policy capacity from government agencies tasked to design and implement it. Identifying the right mix of policy capacity that governments should possess has been made difficult due to conceptual and operational problems. This article addresses the gap by developing a framework that conceptualizes policy capacity as the ability of governments to perform analytical, operational, and political functions. Drawing on the results of an original teacher survey and complementary sources, the article shows that variations on different dimensions of policy capacity have led to significant differences in the effectiveness of capacity development initiatives, especially as perceived by teachers. Therefore, without understanding and catering to the needs of the targets whose capacity is supposedly being developed, capacity development initiatives meant to be supportive are likely to be dissatisfying and disappointing instead. Points for practitioners: This article highlights the importance of policy capacity and further unpacks how its analytical, operational, and political dimensions are essential to the successful delivery of capacity development. Through a rich account of the comparative case of India and China, it illustrates that all these dimensions are important, without any one being a stand-alone panacea. Above all, it is important to pay attention to the recipients of capacity development programs; without doing so, top-down program delivery ignorant of their needs is likely to be poorly received despite the original intention of developing capacity.